Damping contribution of the glass reinforced aluminum laminates epoxy to the aluminum based-sandwich structures. (March 2022) - Kadioglu, Ferhat; Alaboyun, Omer Z.
Despite many potential use of aluminum sandwiches in advanced industries, their poor performance in damping and sound transmission demands new challenges for improvement. This study aims to improve dynamic performance of these sandwiches using hybrid face sheets in the form of Glass Laminate Aluminum Reinforced Epoxy (GLARE). While parameters related to the aluminum honeycomb core were kept constant, the effects of different fiber orientations of the GLARE on the fundamental natural frequency, equivalent flexural modulus, and especially damping values were investigated. The dynamic values of the structures have been measured using a specially designed non-contact vibrating beam test with free-free end conditions. A comparison of the sandwiches with the GLARE and with bare aluminum face sheets has also been made to find out their differences in the dynamic performance. The experimental results were compared to those from a numerical modal analysis via the Altair Hyperworks 2019 Software. The results have shown that the maximum equivalent modulus is obtained from the specimen with the unidirectional (0°) fibers, and the minimum value is from that with the 90° ones. But the opposite is the case if their Specific Damping Capacity values are compared. The values of the specimens with 0°/90° and 0°/45° fibers are on moderate levels. Considerable increments between 54% and 172% are found in the damping values of the specimens with GLAREs, compared to those with the bare aluminum face sheets. The results from the experimental and numerical works have been found in a good agreement.